2002
DOI: 10.1177/0146167202289004
|View full text |Cite
|
Sign up to set email alerts
|

Intragroup and Intergroup Evaluation Effects on Group Behavior

Abstract: Groups differ in the prestige they are accorded by outgroups, and individuals differ in how much respect they receive from their group. The authors orthogonally varied both types of social evaluation-intergroup and intragroup-to assess their joint effects on reward allocations and the amount of time donated to work on a group activity that could satisfy either personal or group goals. Respected members of a devalued group were the most inclined to withhold rewards from the outgroup, and they donated the greate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
171
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 153 publications
(177 citation statements)
references
References 32 publications
6
171
0
Order By: Relevance
“…Nurses continue to identify that improving their work environment will improve job satisfaction, which is the most important solution to resolving the nursing shortage (Krueger, 2002). Respect is perceived in terms of (1) inclusion within a group captured in terms of perceived liking (Branscombe et al, 2002); (2) fair treatment (e.g. Huo & Molina, 2006); (3) appraisal of qualities (Prestwich & Lalljee, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Nurses continue to identify that improving their work environment will improve job satisfaction, which is the most important solution to resolving the nursing shortage (Krueger, 2002). Respect is perceived in terms of (1) inclusion within a group captured in terms of perceived liking (Branscombe et al, 2002); (2) fair treatment (e.g. Huo & Molina, 2006); (3) appraisal of qualities (Prestwich & Lalljee, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Above all, research has shown that lower identifiers emphasize group heterogeneity as a way of individually distancing themselves from a negative group in their eyes (Doosje, Spears & Koomen, 1995;Ellemers, et al, 1997). In short we used ingroup homogeneity as an indirect indicator of genuine group loyalty, because it is sufficiently unobtrusive to avoid self-presentational concerns that might interfere with the predicted effects.In Study 2, we adopted the second more behavioral route to assessing loyalty by measuring willingness to exert an effort on behalf of the group (Branscombe, Spears, Ellemers, & Doosje, 2002;Ouwerkerk, Ellemers, & De Gilder, 1999). The willingness to work for the group measure should be easily identified by group members as directly tapping group loyalty, but in this case commitment actually implies personal costs and should therefore detect genuine loyalty as opposed to mere self-presentation.…”
mentioning
confidence: 99%
“…found that respect positively increased in-role and extra-role behaviors (Tyler & Blader, 2002) and members' willingness to spend time improving the collective (Branscombe et al, 2002). Building on this, the data revealed that receiving personalized respect appeared to increase Televerde employees' in-role performance.…”
Section: Performance-oriented Outcomes Prior Quantitative Respect Rementioning
confidence: 72%
“…Researchers have made significant empirical strides, identifying desirable effects of perceived intragroup respect. For instance, Branscombe, Spears, Ellemers, and Doosje (2002) found that members of a group who perceived respect (from other members) were willing to donate time to improving the image of the group above and beyond the time they were willing to invest in improving their personal image. Additionally, feeling respected leads to increased identification and cooperation with a group (Smith, Tyler, & Huo, 2003).…”
Section: Research On Respectmentioning
confidence: 99%